It takes two: how Eurosceptic public opinion and party divisions influence party positions. Issue 4 (4th July 2017) - Spoon, Jae-Jae; Williams, Christopher
Abstract: Do parties respond to voters' preferences on European integration in elections to the European Parliament (EP)? Following recent research that shows political party responsiveness to Eurosceptic attitudes during EP elections is conditioned by party characteristics, this article seeks to understand how party unity on European integration affects party responsiveness to Euroscepticism. It argues that when Eurosceptic attitudes among voters are high and the parties are divided in their position on European integration, parties will be more responsive to voters and take a more Eurosceptic position. To test the theoretical expectations, the study uses data from the Chapel Hill Expert Survey, the Euromanifestos Project, and European Election Study for 1989–2009 for over 120 parties across 20 European Union member states. The findings have important implications for understanding the nature of democratic representation in the European Union.